2020
DOI: 10.1002/fsn3.1440
|View full text |Cite
|
Sign up to set email alerts
|

Functional quality evaluation and shelf life study of synbiotic yacon juice

Abstract: The research aimed to utilize the prebiotic potential of yacon fruit by preparation of synbiotic yacon juice containing probiotic microorganism Lactobacillus acidophilus (La5) and studying the changes in physicochemical properties during storage. The fresh juice extracted was added with probiotic microorganism and was subjected for storage at refrigerated (4°C) and room condition (25°C) along with control (nonfermented) juice. The viability of probiotic strains in the juice was found to be at the satisfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Similar results were also observed by Dahal et al. (2020) for synbiotic yacon juice, where the probiotic viability of Lactobacillus acidophilus (La5) in the juice was within the satisfactory level (10 6 CFU/ml) for 15 days in room condition. Moreover, they also reported that the lower counts of yeast and mold and the absence of coliform in the synbiotic juice, even after 15 days of storage, allow the synbiotic juice to be consumed commercially.…”
Section: Resultssupporting
confidence: 88%
“…Similar results were also observed by Dahal et al. (2020) for synbiotic yacon juice, where the probiotic viability of Lactobacillus acidophilus (La5) in the juice was within the satisfactory level (10 6 CFU/ml) for 15 days in room condition. Moreover, they also reported that the lower counts of yeast and mold and the absence of coliform in the synbiotic juice, even after 15 days of storage, allow the synbiotic juice to be consumed commercially.…”
Section: Resultssupporting
confidence: 88%
“…A study used probiotic L. acidophilus -containing yacon roots to make symbiotic yacon juice. In refrigerated and room conditions, the juice’s probiotic strain viability was reasonable (10 6 CFU/ml) for 15 and 27 days, respectively [ 75 ]. Lactobacillus acidophilus and L. plantarum at 37 ° C, both strains that flourished in juice combinations, contained respective concentrations of around 9 and 8 log CFU/ml following 24 h of fermentation [ 76 ].…”
Section: Probiotic Vegetable Juicesmentioning
confidence: 99%
“…The total soluble solids in probiotic fruit and vegetable juices are reduced during fermentation and storage. A study showed that after 15 and 27 days of storage, the total soluble solid in symbiotic yacon juice containing L. acidophilus reduced from 7.8 to 5.3 and 5.5, while the acidity rose from 0.067 to 1.02 and 0.80 [ 75 ]. By adding 1% L. plantarum , 1% L. fermentum , and a combination of 0.5% each to apple and star fruit juices, three probiotic juice samples were produced and demonstrated that with longer storage times, the pH, protein content, and total soluble solids of probiotic juices all slightly decreased [ 41 ].…”
Section: Physiochemical Changes In Probiotic Fruit and Vegetables Juicesmentioning
confidence: 99%
“…Currently, there is a growing demand among vegan consumers for probiotic beverages like WK (Dahal et al., 2020 ; Moretti et al., 2022 ; Mousavi et al., 2023 ). However, the available information on storing water kefir grains was limited.…”
Section: Introductionmentioning
confidence: 99%